Balance Scorecard Analysis of Amil Zakat Institute (Case Study of LAZISMU South Sulawesi) - Rizaldi, Muh; Suarni, Agusdiwana; Hasanuddin, Hasanuddin (Publication Division of International Ecsis Association, 2023)
This study aims to find out about the performance of LAZISMU South Sulawesi. This study uses a qualitative approach that aims to find out the level of performance of an institution so that the data collected will be measured by certain criteria or standards and researchers want to know the level of achievement of an institution. The subjects of his research were employees and members of LAZISMU. The object of this study is the performance of the amil zakat infaq and alms institutions of LAZISMU South Sulawesi with a Balance scorecard approach. Data Collection Techniques include observation, interviews, and documentation. The results of this study on the performance of the institutions of alms, zakat, infaq, and alms Muhammadiyah South Sulawesi are quite good, it's just that for amils in charge of the distribution section is still minimal. Lembaga Amil Zakat Infaq dan Sedekah Muhammadiyah (LAZISMU) is measured by the Balance scorecard approach which contains five components of performance measurement, namely financial perspective performance, customer perspective performance, internal business perspective performance, learning and growth perspective performance.